2020
DOI: 10.20944/preprints202009.0636.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Students’ Experience with the Transition from Primary to Secondary School on Self-Regulated Learning and Motivation

Abstract: Transition from primary to secondary school is more successful when students’ learning is consistent. Students are also more likely to enjoy the school, engage with learning, and have a high academic achievement in the secondary school when they feel motivated. This is a critical aspect especially in cases when global pandemics situations allow only the online schooling opportunity. Students that are away from school lack the traditional sources of motivation and self-regulated learning skills, thus … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The time spent away from school will have a greater impact in grades where children have to achieve an important learning outcome, such as reading and writing in the last year of preschool [ 45 ]. Nevertheless, sociologists and educationalists assure that the youthfulness of these children and the good work of their teachers will allow them to recover the knowledge missing during lockdown in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…The time spent away from school will have a greater impact in grades where children have to achieve an important learning outcome, such as reading and writing in the last year of preschool [ 45 ]. Nevertheless, sociologists and educationalists assure that the youthfulness of these children and the good work of their teachers will allow them to recover the knowledge missing during lockdown in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…The Primavera programme met most of the recommended criteria for the development of prevention programmes against alcohol and tobacco use in schools: beyond the need to address substance use issues, it aims more widely to develop psychosocial skills [ 7 , 8 , 11 , 17 , 19 , 21 ], it is multimodal [ 8 , 11 , 17 , 19 ] and pluri-annual [ 9 , 12 ]. In addition, the programme is implemented across the primary–secondary school transition, a critical period in terms of emotional, social, and academic adjustment [ 13 , 14 , 15 ]. This programme is in current use in French schools by several trained teams.…”
Section: Discussionmentioning
confidence: 99%
“…For prevention actions to be efficacious in improving risks awareness and social skills, it is important to implement early interventions; it has been suggested that preventive actions among young people should be initiated early on in their lives [ 7 , 8 , 9 , 10 ]. Continuity in action over several school years, especially during the transition between primary and secondary school, could also be a factor predictive of efficacy [ 8 , 9 , 11 , 12 , 13 , 14 , 15 ]. Concerning the specific qualities that make prevention programmes at school efficacious among schoolchildren, a few studies have shown the benefits of a theoretical base integrating the promotion of health and the development of psychosocial skills through the use of individuals’ experiences and resources derived from their environment [ 8 , 10 , 11 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%